2022
DOI: 10.1039/d1cc07060f
|View full text |Cite
|
Sign up to set email alerts
|

Bis(1-bora-4-phosphorinane) ring closure at Cp*M (M = Fe, Co) complexes

Abstract: Bis(1-bora-4-phosphorinane) metal complexes have been synthesized using a Cp*M-protecting (M = Fe, Co, Cp* = C5Me5-) strategy and structurally authenticated by NMR spectroscopy and single crystal X-ray diffraction. Synthesis of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Recent work in our laboratory has concentrated on the preparation of diphosphine ligands featuring borane groups in the secondary coordination sphere (SCS) [19–22] . We and others have shown that these groups participate in chemical transformations, offering stabilization to Lewis basic substrates such as amides, sulfides, hydroxides, alkyl anions, hydrides, pyridines, and more [23–27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work in our laboratory has concentrated on the preparation of diphosphine ligands featuring borane groups in the secondary coordination sphere (SCS) [19–22] . We and others have shown that these groups participate in chemical transformations, offering stabilization to Lewis basic substrates such as amides, sulfides, hydroxides, alkyl anions, hydrides, pyridines, and more [23–27] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in our laboratory has concentrated on the preparation of diphosphine ligands featuring borane groups in the secondary coordination sphere (SCS). [19][20][21][22] We and others have shown that these groups participate in chemical transformations, offering stabilization to Lewis basic substrates such as amides, sulfides, hydroxides, alkyl anions, hydrides, pyridines, and more. [23][24][25][26][27] As an extension of our work, we were interested in preparing an unsymmetrical diphosphinoethane ligand containing a single borane unit, allowing for targeted reactivity between the borane and a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, we previously s h o w e d t h a t [ F e ( d v p e ) 2 C l 2 ] ( d v p e = 1 , 2bis(divinylphosphino)ethane) does not undergo productive hydroboration, instead the ligand is lost as a Lewis acid/base pair, accompanied by [FeCl 2 (THF) x ]. 14 It was therefore imperative to first install a Cp* (Cp* = C 5 Me 5 − ) ligand to prepare [Cp*Fe(dvpe)Cl], allowing for successful hydrofunctionalization (ring-closure) (Figure 1B). As a furtherance to our work in this area, we now disclose several complexes of the type [Cp*Fe(diphosphine)(X)] (X = Cl, H) that bear Lewis acids in their SCS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our group has contributed a number of diphosphine ligands where unsaturated R-groups serve as modifiable sites for the installation of Lewis acids (boranes; −BR 2 ) via hydroboration. In most cases, installation is performed post-coordination, the success of which depends on the nature of the metal starting material. As an example, we previously showed that [Fe­(dvpe) 2 Cl 2 ] (dvpe = 1,2- bis (divinylphosphino)­ethane) does not undergo productive hydroboration, instead the ligand is lost as a Lewis acid/base pair, accompanied by [FeCl 2 (THF) x ] . It was therefore imperative to first install a Cp* (Cp* = C 5 Me 5 – ) ligand to prepare [Cp*Fe­(dvpe)­Cl], allowing for successful hydrofunctionalization (ring-closure) (Figure B).…”
Section: Introductionmentioning
confidence: 99%
“…). Within the context of small molecule functionalization, secondary sphere acidic groups can modify the electronic structure of metal-coordinated intermediates and ultimately introduce divergent reactivity for complexes with/without secondary sphere acids. ,, Exogenous borane Lewis acids have been shown to influence substrate binding/activation, although strong Lewis acids are typically required. , One strategy to lower the acidity required for substrate binding is to decrease the entropic penalty of Lewis acid/substrate binding. A highlight of this approach was work by Miller, Labinger, and Bercaw, who demonstrated that a borane-tethered monodentate phosphine ligand enabled Re-mediated CO reductive coupling. , Related examples with bidentate phosphines are rare, and multi-borylated bis­(phosphino)­ethanes were recently reported by Drover and co-workers as a strategy to promote hydride transfer …”
Section: Introductionmentioning
confidence: 99%